Is India on a path to reduce the tobacco industry’s influence in tobacco control? Insights from the Global Tobacco Industry Interference Index (2019–2023) - Goel, Sonu; Walia, Diksha; Bhojani, Upendra; Bhatnagar, Nandita; Chopra, Mrinalima (Frontiers in Public Health, 2024)
Introduction The tobacco industry (TI), driven by profit motives, consistently conceals health risks through deceptive strategies, notably in countries like India. These tactics create vulnerabilities that hinder effective tobacco control measures and enable the TI to exploit legal gaps. Understanding these TI strategies is essential for policymakers to take appropriate preventive and corrective measures in order to limit tobacco industry interference (TII) in policy-making. The study aims at understanding the trend of TII in India between 2019 and 2023. Methodology The secondary data from the Global Tobacco Industry Interference report, consisting of seven major domains of the TII index, viz. policy participation, corporate social responsibility (CSR) activities, industry benefits, unnecessary interaction, transparency, conflict of interest, and preventive measures, were retrieved. A composite score was obtained after adding scores of different domains, for each year. Results The findings of the study demonstrated an initial improvement in India’s implementation of WHO FCTC Article 5.3, as evidenced by a decreasing score between 2019 and 2021. However, this trend halted in 2023, with data showing a slight increase in the score. When compared with other Asian countries, India shows marginal improvement in score than Cambodia, China, Indonesia, Lao PDR, Malaysia, Myanmar, Nepal, Philippines, Thailand, and South Korea. Some of the countries in the region, including India, Pakistan, Bangladesh, Sri Lanka, Myanmar, Brunei, China, and Vietnam experienced a decline in TII. Discussion There has been a rise in CSR activities, forms of unnecessary interactions of TII with policymakers, and participation in policy development; however, improvements are observed in providing benefits to the TI, conflict of interest, and preventive measures. In order to fortify the regulatory framework, it is imperative to create awareness among stakeholders on conflict of interest, denormalize corporate social responsibility (CSR) initiatives by the TI, provision of a watchdog for TII in the country and “whole of government” approach in implementation of FCTC Article 5.3.